MODELING OF SATELLITE CHANNEL FOR TRANSMISSION OF ADS-B MESSAGES - Харченко, В.П.; Барабанов, Ю.М.; Грехов, A.M. (Proceedings of National Aviation University (archive), 2012)
The model of communication channel “aircraft – satellite – ground station” was built and used for modeling of ADS-B messages transmission with the help low-orbit satellite complex Iridium. Dependences of Bit Error Rate on type of signal modulation, losses on a line, diameter of antennas, nonlinearity of high power amplifier and satellite repeater gain and received.